TOURIST IMAGE OF SUMY REGION (BASED ON SOCIOLOGICAL RESEARCH) - BerestokА. А. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
Topical issue in tourism development of Sumy region is the problem of tourist image formation as a source of regional competitiveness. The purpose of the article was to determine the tourist attractiveness of Sumy region as the result of the poll, which was attended by residents of different regions of Ukraine. It was found out that of about 3,000 respondents only 20% visited Sumy region with the purpose of tourism. The most visited areas are Sumy, Akhtyrka, Konotop, Trostyanets and Putivl. Рromising types of tourism in the Sumy region is guided tourism, water, religious and rural tourism. Sumy region, according to respondents, in general, is attractive to tourists, and the main problems of tourism development are: insufficient funding for tourism, low availability of tourist infrastructure, poor road surfaces in the region, lack of advertising of tourist facilities and so on. Most of these problems, unfortunately, are systemic in nature and are inherent in most regions of the country. Аt the regional level, local authorities should pay attention to providing more information on tourist resources of Sumy region, as well as the availability of such information for most population. In addressing issues Sumy region has prospects for being a competitive region on the tourist market of Ukraine.